Kaji Eksperimental Sistem Sirkulasi Air Tanaman Hidroponik Tenaga Surya - Neylan Nurina; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The circulation of water in hydroponic crops is one ting that is very important in hydroponic plant cultivation, because the circulation of water is needed by plants. Hydroponic water needs at less than the water needs of plants cultivated in the ground. Hydroponics is defined as a way of farming without using soil. The circulation of water in the hydroponic growing methods required pembuatanya system design with the motor as the driving force of water flow, and solar panels as a powerhouse. Solar panels are one type of alternative energy that utilizes the power from solar energy into electrical energy. The motors used to circulate water are aquarium motors or aquarium pumps, the pump capacity used in this research is 25 watts with head 1.2 meters (maximum) and water debit 1300 liter / hour.Keywords: Hydroponics, Solar Panels, Submersible Water Pump.